Big Ideas What is an artistic director?' ask - Jackson, Jennifer; Crow, Susan (Dance Books Ltd., Alton,Hampshire (UK), 2001)
The Big Discussion Forum is an ongoing series that seeks to open up issues relating to ballet in today's world. BIG, which stands for Ballet Independents Group, was founded by Jennifer Jackson and Susan Crow. Early this year, they invited a trio of distinguished speakers - each with a particular perspective on ballet and with experience of leadership - to consider what it means to direct a ballet company. Lynn Seymour, dancer, choreographer, former artistic director of the Spitalfields Festival, and John Drummond, formerly Director of the Proms and the Edinburgh Festival and Controller of Radio 3, member of Birmingham Royal ballet board and author of Speaking of Diaghilev, reflected on the changes of the last century and challenges of the current one for the art form and those leading its institutions. PALABRAS CLAVE: Ballet Independents Group, artistic directors, responsibilities.